PENERAPAN MODEL FLIPPED LEARNING TERHADAP PENINGKATAN HASIL BELAJAR SISWA PADA MATERI PERTIDAKSAMAAN IRASIONAL - Ahmad Hassan Triaji; Aflich Yusnita Fitrianna; Luvy Sylviana Zanthy (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2022)
This research aims to analyze learning outcome of grade X students in one of the Public Senior High Schools in Cimahi on the subject of irrational inequalities, using the learning method of flipped learning. Research method used is classroom action research and the subjects being researched are 18 students of grade X IPA. On the first cycle, conventional learning method is used, continued by the second cycle, which used flipped learning model. The data collection technique is using observation, documentation, and 4 essay test question that suitable with indicator of competence achievement. Improvement of learning outcome are then reviewed frommstudents grades in comparison with the school’s KKM on the first as well as the second cycle. In conclusion, there are 61% of student who do not pass the KKM on the first cycle, however by using the flipped learning model on the second cycle, there are only 22% of students who do not pass. It shows that the model gives a better influence toward students’ learning outcome compared to the convensional learning model.